ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEWIRAUSAHAAN TERHADAP PENINGKATAN EKONOMI PADA IBU RUMAH TANGGA DI WILAYAH KOTA BINJAI - FINA JAYANTI; ANGELINA FRISCILIANGI (LP2MTBM MAKARIOZ, 2021)
During the period of 2018-2020 the number of Housewives who became entrepreneurs was decreasing, which was due to the fact that there were still several Housewives who opened businesses just participating and only wanted to meet the needs of life and help their husbands, so they did not have careful planning to design a business design, thus making business income not increase significantly. In addition, Housewives who open a business do not have the qualified ability to become entrepreneurs and do not yet have the spirit for entrepreneurship, so that economic improvement and also business income cannot increase significantly and tend to remain and cannot develop or even many go out of business due to lack of knowledge, business design that is not good, and the absence of enthusiasm to improve business development into a large business. This study aims to find out how the influence of the creativity of designing business designs owned by Housewives in Binjai City, the entrepreneurial ability of Housewives in Binjai City and the entrepreneurial spirit of Housewives in Binjai City on the variables of increasing the economy and business income of Housewives in Binjai City. TThe total population in this study was Housewives in Binjai City who became entrepreneurs as many as 1175 people, where the sampling technique used simple random sampling with a total sample of 39 Housewives in Binjai City who became entrepreneurs. The results of the study can be concluded that simultaneously and partially the variables of creativity in designing business designs owned by Housewives in Binjai City, the entrepreneurial ability of Housewives in Binjai City and the entrepreneurial spirit of Housewives in Binjai City affect the variables of improving the economy and business income of Housewives in Binjai City.